Scoping report: current status of index-based insurance in Bangladesh - Ahmed, T. (2014)
With current and anticipated increases in magnitude of extreme weather events and a declining consistency in weather patterns, particularly challenging for agriculture, there has been a growing interest in weather index-based insurance (IBI) schemes in Bangladesh. A number of weather index-based insurance products have already been tested and applied across Asia and Africa, with varying degrees of success, as a mechanism to improve livelihood security by enabling vulnerable populations to transfer risk associated with climate change, extreme weather events and other hazards. In the process, these efforts have generated important new knowledge on how these schemes can be designed and implemented for optimal results. However, the practice of index-based insurance is still limited in Bangladesh, and the experience and knowledge generated by the different stakeholders involved needs to be better communicated. To identify and facilitate the diffusion of knowledge and best practices in this unique field, Worldfish held a two-day workshop for experts and practitioners who are working on this issue in Bangladesh. This event aimed to map past and present index-based insurance schemes that have been undertaken in Bangladesh, and to facilitate knowledge sharing and capacity building among relevant organizations. Prior to this event, the International Centre for Climate Change and Development (ICCCAD) conducted this scoping study to inform the design and objectives of the two-day workshop.